Some modern aspects of the customs and tariff regulation of trade at the level of the Customs Union (Journal of actual problems of jurisprudence, 2018)
In an article written on the basis of the center of trade policy materials, discusses some modern aspects of customs and tariff regulation of trade at the level of the Customs Union. As you know, this regulation is part of the foreign policy of the state with which the state has the possibility to influence the country’s economic position in the world economic position of the individual goods and producers on the domestic market and to supplement the state budget. From 1 January 2010, Kazakhstan began to use one with Russia and Belarus trade regime for the import of goods from third countries. Key words: customs and tariff regulation, Customs Union.